Proliferation of SARS-CoV-2 B.1.1.7 Variant in Pakistan-A Short Surveillance Account - Umair, Massab; Salman, Muhammad; Rehman, Zaira; Badar, Nazish; Ali, Qasim; Ahad, Abdul; Ikram, Aamer (Frontiers in Public Health, 2021)
The emergence of a more transmissible variant of SARS-CoV-2 (B1. 1.7) in the United Kingdom (UK) during late 2020 has raised major public health concerns. Several mutations have been reported in the genome of the B.1.1.7 variant including the N501Y and 69-70deletion in the Spike region that has implications on virus transmissibility and diagnostics. Although the B.1.1.7 variant has been reported by several countries, only three cases have been reported in Pakistan through whole-genome sequencing. Therefore, the objective of the study was to investigate the circulation of B.1.1.7 variant of concern (VOC) in Pakistani population. We used a two-step strategy for the detection of B.1.1.7 with initial screening through TaqPathTM COVID-19 CE-IVD RT-PCR kit (ThermoFisher Scientific, Waltham, US) followed by partial spike (S) gene sequencing of a subset of samples having the spike gene target failure (SGTF). From January 01, 2021, to February 21, 2021, a total of 2,650 samples were tested for SARS-CoV-2 and 70.4% (n = 1,867) showed amplification of all the 3 genes (ORF, N, and S). Notably, 29.6% (n=783) samples have been SGTF that represented numbers from all the four provinces and suggest a rather low frequency during the first 3 weeks of January (n = 10, n = 13, and n = 1, respectively). However, the numbers have started to increase in the last week of January, 2021. During February, 726 (93%) cases of SGTF were reported with a peak (n = 345) found during the 3rd week. Based on the partial sequencing of SGTF samples 93.5% (n = 29/31) showed the characteristic N501Y, A570D, P681H, and T716I mutations found in the B.1.1.7 variant. In conclusion, our findings showed an upsurge of B.1.1.7 cases in Pakistan during February, 2021 affecting 15 districts and warranting large scale genomic surveillance, strengthening of laboratory network and implementation of appropriate control measures in the country.